Does substance use affect academic performance? - Daniel I. Rees (IZA World of Labor, 2019)
A non-trivial portion of traffic fatalities involve alcohol or illicit drugs. But does substance use—which is linked to depression, suicide, and criminal activity—also reduce academic performance? Recent studies suggest that the consumption of alcohol has a negative effect on the grades of university students. Likewise, there is evidence that marijuana use reduces the academic performance of university students. Although students who use illicit substances are more likely to drop out of high school than those who do not, this may reflect the influence of other, difficult-to-measure factors at the individual level, such as personality.
Keywords: I1; I2; K4; 330; alcohol; marijuana; school dropout; human capital; grade point average